Factors Influencing Motivation in Learning English of Mangusada Badung General Hospital Staff - Ketut Santi Indriani (OKARA: Jurnal Bahasa dan Sastra, 2020)
English as a means of communication is used in many fields, such as health, economic, etc. This research was conducted at Mangusada Badung General Hospital located in the Badung regency of Bali Province. Mangusada Badung General Hospital has a high frequency of giving health services to foreign tourists. The ability to communicate in English is not only needed by medical personnel who are directly serve the foreign patients but also needed by other hospital staff, such as public relations staff, telephone operators, non-medical laboratory staff, registration staff, and others. This research is aimed to identify the influencing factors of motivation in learning English of Mangusada Badung General Hospital staff. The data in this research were collected through a questionnaire method with closed questions which were distributed to 50 respondents of staff from various divisions at Mangusada Badung General Hospital. The data obtained were analyzed using the motivation theory delivered by Gardner, William & Burden, and Finocchiaro. From the research, it is found that the five categories of influencing factors of motivation (personality, behavior, the role of teacher, learning style, and language relation) have almost the same portion in influencing the motivation in learning English.